Glutamate-responsive translation of dendritic GSK3β mRNA triggers a cycle for amplification of reactivated preexisting GSK3β that is indispensable for tau hyperphosphorylation. (October 2020) - Tanaka, Toru; Ohashi, Sachiyo; Takashima, Akihiko; Kobayashi, Shunsuke
Abstract: The molecular mechanism responsible for hyperphosphorylated tau accumulation in dendrites of Alzheimer's disease (AD) neurons has not been fully clarified. Recently, we reported that tau mRNA is distributed into dendrites, and that translation and phosphorylation of tau protein are immediately enhanced in response to glutamatergic stimulation. Here, we focused on dendritic glycogen synthase kinase 3β (GSK3β), a key enzyme for tau phosphorylation, and investigated the mechanism responsible for the neural stimulation-induced hyperphosphorylation of the newly translated dendritic tau protein. We found that GSK3β mRNA was also distributed into dendrites of cultured hippocampal neurons, and that a glutamate-dependent slight increase of translation occurred in a short time. Concomitantly, dephosphorylation at the Ser9 residue of the preexisting GSK3β, which reactivates this kinase, was strongly induced without an increase of its phosphatase PP1 or a decrease of the PP1 inhibitor I-2. Instead, I-2 phosphorylation was observed, suggesting disinhibition of PP1. This glutamate-dependent phosphorylation of I-2 and the dephosphorylation of preexisting GSK3β were abolished in the presence of GSK3β inhibitors. Interestingly, translational obstruction of GSK3β mRNA also canceled these reactions. These results indicate that dendrites exhibit a glutamate-responsive cycle for amplification of reactivated preexisting GSK3β operating via PP1 disinhibition, whose activation requires neural activity-dependent translation of dendritic GSK3β mRNA. This would explain why a slight increase of dendritic GSK3β is sufficient to trigger hyperphosphorylation of significantly increased tau protein. Highlights: GSK3β mRNA is translated in dendrites in response to glutamatergic stimulation. Glutamate induces reactivation of preexisting GSK3β and tau phosphorylation in dendrites. Glutamate induces I-2 phosphorylation, resulting in PP1 disinhibition. GSK3β inhibition abolishes the glutamate-dependent actions on I-2 and GSK3β. The glutamate-dependent slight increase of GSK3β triggers an amplification cycle of reactivated GSK3β in dendrites.